Odontologia digital aplicada ao processo ensino-aprendizagem e acurácia do escaneamento intraoral em diferentes substratos dentários. - Moura, Guilherme Faria (2020)
Digital dentistry presents an increasing demand in the development of dental processes. The search for improvement in the accuracy of restorations begins when the practitioner perception about the precision of dental preparations evolves. This understanding should initiate even during the training process of undergraduate students and involves recognizing the relationship between image acquisition through intraoral scanning and the substrate to be scanned. This study was divided into three specific objectives: Objective 1: to evaluate and compare the student scores during a full crown preparation process in the fixed prosthodontics course using manual and digital tools; Objective 2: correlate the assessment of the full crown preparation carried out by the student manually, by the teacher manually and using 3D software, to increase the agreement between teacher and student; Objective 3: to assess whether the use of a second finishing instrument on the cervical margin of a full crown preparation, as well as the conditions of the oral environment, influence the accuracy of the digital file generated by the intraoral scanner. The evaluation of the different techniques for scoring dental preparations made by the students showed that for measurable criteria such as axial reduction and occlusion, there was statistical difference for the manual and digital evaluations, in which the digital technique was more accurate. Regarding the agreement between teacher and students using digital methods for assessment, there was moderate to low correlation level among them. When evaluating the accuracy of the scans on different dental substrates, the presence of saliva decreased the accuracy of scanning, regardless the substrate and the refinement of the preparation. For the enamel substrate, there was no statistical difference between the use of refining instruments to finish the preparation before scanning; for dentin substrate, the refinement of the preparation improved the scanning efficiency.